Identificação e mapeamento de acupontos reais na topografia anatômica de animais silvestres e sua aplicabilidade em procedimentos clínicos e cirúrgicos - Silva, Taciana de Melo Fernandes (Universidade Federal Rural do Semi-Árido, 2016)
Acupuncture is a therapeutic technique of traditional Chinese medicine, which has been widespread in the West. Defined as a treatment technique with insertion of needles into points (acupoints) exactly pre-set on the body to produce a specific physiological reaction in order to restore the balance between conflicting states function and homeostasis, alternating power states and thus keeping the organization of the organ and the body. Thus, the objective of this study was to map and describe the main acupuncture points on the species Boa constrictor (Jiboia), Six-banded armadillo (Armadillo-peba) Chelonoidis carbonaria (Jabuti-of--red legs) and Iguana iguana (Iguana) as well as their indications to promote therapeutic control of these species. The unprecedented result of the mapping was the discovery of specific acupoints and their therapeutic indications and impedance each, which reflects the resistance and the need for stimulation or greater depth to be effective. In carbonaria Chelonoidis species were discovered a total of 14 acupoints. The species Boa constrictor were found 8 acupoints, the species Iguana 10 acupoints and six-banded armadillo species found 14 acupoints. Since the points have therapeutic effect for many types of syndromes, its mapping allows a better and faster viewing to effect treatment
Identification and mapping in real acupoints surveying animal anatomical wild and its applicability in clinical and surgical procedures
Keywords: Acupuntura; Animais silvestres; Acupontos; Mapeamento; Impedância; Acupuncture; Wild animals; Acupoints; Mapping; Impedance; CIENCIAS AGRARIAS::MEDICINA VETERINARIA